Application of Thermal Response Measurements to Investigate Enhanced Water Adsorption Kinetics in Ball‐Milled C2N‐Type Materials. Issue 12 (13th December 2022) - Du, Shengjun; Leistenschneider, Desirée; Xiao, Jing; Dellith, Jan; Troschke, Erik; Oschatz, Martin
Abstract: Sorption‐based water capture is an attractive solution to provide potable water in arid regions. Heteroatom‐decorated microporous carbons with hydrophilic character are promising candidates for water adsorption at low humidity, but the strong affinity between the polar carbon pore walls and water molecules can hinder the water transport within the narrow pore system. To reduce the limitations of mass transfer, C2 N‐type carbon materials obtained from the thermal condensation of a molecular hexaazatriphenylene‐hexacarbonitrile (HAT‐CN) precursor were treated mechanochemically via ball milling. Scanning electron microscopy as well as static light scattering reveal that large pristine C2 N‐type particles were split up to a smaller size after ball milling, thus increasing the pore accessibility which consequently leads to faster occupation of the water vapor adsorption sites. The major aim of this work is to demonstrate the applicability of thermal response measurements to track these enhanced kinetics of water adsorption. The adsorption rate constant of a C2 N material condensed at 700 °C remarkably increased from 0.026 s −1 to 0.036 s −1 upon ball milling, while maintaining remarkably high water vapor capacity. This work confirms the advantages of small particle sizes in ultramicroporous materials on their vapor adsorption kinetics. It is demonstrated that thermal response measurements are a valuable and time‐saving method to investigate water adsorption kinetics, capacities, and cycling stability. Abstract : Thermal response measurements as well as volumetric water physisorption measurements are applied to study the influence of particle sizes on water adsorption capacity and kinetics. For this, a controlled thermal condensation process followed by a mechanical treatment using a ball mill is applied to synthesize C2 N‐type carbon materials with smaller and larger particle sizes. The nitrogen‐rich surfaces and narrow distributed micropores endow them with remarkable hydrophilic features. Using the InfraSORP technique, a fast and accurate assessment of these properties is demonstrated.